SERVQUAL measurement model and service quality in a private educational institution in Ica, 2022 - Romaní-Pillpe, Guillermo (2023)
Objective. To determine the relationship between the SERVQUAL measurement model and service quality in a private educational institution in Ica (Peru), during 2022. Methods. The study had a quantitative approach, non-experimental design, being an applied research. The population consisted of 31 parents. Two instruments were applied: the adapted SERVQUAL measurement model (22 items) and the service quality measurement model (14 items). Results. The hypothesis was inferred using Spearman's nonparametric rho test. A result of p = 0.01 was obtained to contrast the general hypothesis. Therefore, the correlation was significant enough to accept h1 and reject h0, formulated at the beginning of the research. Conclusion. There is a very strong positive correlation between the SERVQUAL measurement model and the quality of service as perceived by the parents of a private institution in the province of Ica.